Particle swarm optimization effectiveness for selectiveharmonic elimination in multilevel inverters at varyingoutput levels - Hamidi, Muhammad Najwan; Ishak, Dahaman (Majlesi Journal of Electrical Engineering, 2025)
Multilevel inverters (MLI) play a pivotal role in diverse applications, notably solar power generation, owing to their capacity for generating high-quality, multiple-level output voltages with reduced total harmonic distortions (THD) in comparison to traditional inverters. Nevertheless, as MLI levels increase, challenges arise, impacting implementation feasibility due to heightened computational demands for pulse width modulation (PWM) generation. Researchers have inclined towards low-frequency, pre-calculated switching signal methods, although these tend to induce higher output harmonics, particularly at lower levels. This study focuses on studying the significance of employing the particle swarm optimization (PSO) technique to solve selective harmonic elimination (SHE) equations (SHE-PSO) in MLI applications, evaluating its impact on THD at various output levels (3L, 5L, and 7L) within a cascaded H-bridge MLI. Results are compared with simpler methods, namely sine-based calculation (SBC) and Newton Raphson-based SHE (SHE-NR). The findings illustrate that SHE-PSO effectively minimizes lower-order harmonics to as low as 0%, outperforming SBC and NR. However, in terms of THD, SHE-PSO proves advantageous only at 5L, with SHE-NR exhibiting superior performance at other levels. This study concludes that the reduction of lower-order harmonics in MLI does not necessarily translate to an overall improvement in THD, particularly at higher levels.